IDDF2020-ABS-0065 Safety and efficacy of laparoscopic microwave ablation and portal vein ligation for staged hepatectomy (LAPS) in patients with hbv-related hepatocellular carcinoma. (18th November 2020) - Lei, Kai; Chen, Zebin; Chen, Shuling; Liang, Ruiming; Peng, Zhenwei; Peng, Sui
Abstract : Background: Associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) has high morbidity and mortality. In this study, the safety and efficacy of a modification of ALPPS (laparoscopic microwave ablation and portal vein ligation for staged hepatectomy, LAPS) were compared with the classic ALPPS in patients with HBV-related hepatocellular carcinoma (HCC). Methods: Patients who were diagnosed with HCC and were considered to have insufficient future liver remnant (FLR) were enrolled. In stage I, a microwave ablation (MWA) device was used to cauterise along the planned transection plane to form a coagulum avascular area. When the FLR reached above 40%, hepatectomy was performed in stage II along the coagulum area established previously. After two stages, operative morbidity, mortality, increase in FLR, operative time and blood loss were evaluated. Results: Between April 2013 and September 2019, 7 patients with HBV-related HCC were treated with the LAPS procedure, and 14 patients were treated with the ALPPS procedure. No major complications (Clavien-Dindo IIIa) occurred after 1 stages of the LAPS group, while the ALPPS group were 21.4% (3/14). Completion rate of secondary surgery of the LAPS and the ALPPS was 85.7% (6/7) and 78.6% (11/14). The incidence of major complications was 36.4% (4/11) of the ALPPS group and 50.0% (3/6) of the LAPS group after the 2 stages operation. One patient died of the ALPPS group. Additionally, the median increase in FLR, median operative time and blood loss during the two stages of the LAPS were similar to those subjected to ALPPS. Conclusions: LAPS has a potential advantage in eliminating major complications of PHLF associated with classic ALPPS. LAPS may achieve the same effect of promoting significant growth of the FLR in patients with HBV-related HCC, albeit at the cost of longer interval time.